1988
DOI: 10.1159/000174383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mitral Valve Prolapse in Chronic Lymphocytic Thyroiditis and Nongoitrous Hypothyroidism

Abstract: An increased prevalence of mitral valve prolapse has been found in Graves’ disease and a common autoimmune etiology has been suggested for both disorders. We investigated the prevalence of mitral valve prolapse in 87 patients with autoimmune chronic lymphocytic thyroiditis, 50 patients with nongoitrous hypothyroidism and 111 healthy control subjects. Mitral valve prolapse was found in 16.09% of patients with chronic lymphocytic thyroiditis compared to 6 and 5.4% in nongoitrous hypothyroidism and normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In hypothyreosis, bradycardia, reversible impairment of myocardial contractility, an increase in peripheral vascular resistance and diastolic hypertension are known, and elevated, low-density lipoprotein (LDL) cholesterol levels too (16). There is also an association of mitral-valve prolapse with auto-immune thyroid diseases (18). Cardiovascular changes have been reported in patients treated with thyrotropin-suppressive doses of thyroxine, including a shortening of the systolic time intervals, a slight increase in the frequency of atrial premature beats and a modest degree of left-ventricular hypertrophy (19 -22), changes that may be counteracted by the concomitant administration of beta-blocking agents (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…In hypothyreosis, bradycardia, reversible impairment of myocardial contractility, an increase in peripheral vascular resistance and diastolic hypertension are known, and elevated, low-density lipoprotein (LDL) cholesterol levels too (16). There is also an association of mitral-valve prolapse with auto-immune thyroid diseases (18). Cardiovascular changes have been reported in patients treated with thyrotropin-suppressive doses of thyroxine, including a shortening of the systolic time intervals, a slight increase in the frequency of atrial premature beats and a modest degree of left-ventricular hypertrophy (19 -22), changes that may be counteracted by the concomitant administration of beta-blocking agents (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…2 Some studies report an increased prevalence of MVP in heritable connective tissue disorders 3 and in organspecific autoimmune disorders such as autoimmune thyroid diseases. [4][5][6][7] Specifically, in patients with autoimmune thyroid diseases, we have previously reported an increased prevalence of further indices of autoimmunity in the group who also had MVP. 4 Some further studies have also reported an increased frequency of MVP in systemic lupus erythematosus (SLE); 8,9 and recently in Crohn's disease.…”
Section: Introductionmentioning
confidence: 90%
“…An increased prevalence of MVP has been reported in Graves' disease and chronic lymphocytic thyroiditis, but the pathophysiological mechanisms linking MVP and autoimmune thyroid disease are still not understood. [7][8][9][10][11] In recent years, a germline mutation of the TSHR gene (P639S) was reported to be associated with thyrotoxicosis and MVPS in a Chinese family.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the prevalence of MVP is significantly elevated in Graves' disease and chronic lymphocytic thyroiditis, but not in toxic multinodular goiter. [7][8][9][10] The pathophysiological mechanisms linking MVP and autoimmune thyroid disease are still not understood. It has been suggested that human leukocyte antigen genes may explain the linkage between Graves' disease and MVP.…”
mentioning
confidence: 99%